Cortical plasticity after hand prostheses use: Is the hypothesis of deafferented cortex “invasion” always true? - Granata, G.; Valle, G.; Di Iorio, R.; Iodice, F.; Petrini, F.M.; Strauss, I.; D'anna, E.; Iberite, F.; Lauretti, L.; Fernandez, E.; Romanello, R.; Stieglitz, T.; et al. (Clinical neurophysiology, 2020)
•The invasion and persistence of deafferented cortex after amputation coexist.•The target is essential for investigating motor brain plasticity in amputees.•This study boosts against a direct role of motor cortical changes on PLP genesis. To study motor cortex plasticity after a period of training with a new prototype of bidirectional hand prosthesis in three left trans-radial amputees, correlating these changes with the modification of Phantom Limb Pain (PLP) in the same period. Each subject underwent a brain motor mapping with Transcranial Magnetic Stimulation (TMS) and PLP evaluation with questionnaires during a six-month training with a prototype of bidirectional hand prosthesis. The baseline motor maps showed in all three amputees a smaller area of muscles representation of the amputated side compared to the intact limb. After training, there was a partial reversal of the baseline asymmetry. The two subjects affected by PLP experienced a statistically significant reduction of pain. Two apparently opposite findings, the invasion of the “deafferented” cortex by neighbouring areas and the “persistence” of neural structures after amputation, could vary according to different target used for measurement. Our results do not support a correlation between PLP and motor cortical changes. The selection of the target and of the task is essential for studies investigating motor brain plasticity. This study boosts against a direct and unique role of motor cortical changes on PLP genesis.